FACTORS INFLUENCING THE EVOLUTION OF YOUTH TRAVEL - Student Claudia MOISĂ (Management & Marketing)
Youth travel is an important part of global tourism, consequently, getting to know the evolution of this form of tourism requires an approach of the aspects regarding the permissive and restrictive factors that influence the youth travel dynamic worldwide. In terms of the factors that influence youth travel, we highlighted these two categories of factors (permissive and restrictive) and, within each category, we tried to singularize the influence of every factor over youth travel.